Etos Kerja Islam Terhadap Karyawan Perwakilan Kantor Urusan Agama - Ana Putri Dyfani; Durrotun Nadhifah; Marisa Amini; Ani Qotuz Zuhro’ Fitriana (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2023)
This study tries to ascertain how KUA officials in the Anchor Area use the Islamic work ethic. This investigation employs an obvious subjective examination methodology. Data collecting methods included observations, documentation, and interviews. The data from this investigation were analyzed using the triangulation approach. Based on the results of this study, KUA employees in the Jangkar District have begun to work according to the Al-Quran and Hadith in order to demonstrate an Islamic work culture. They achieve this through having a sincere, truthful, consistent, courageous, and courageous to accept responsibility and consequences attitude. The Islamic work ethic followed by employees led to improvements in both employee performance and customer satisfaction with the services rendered by KUA staff.